Tutoring and Support for PhD Students: A Proposed Plan - Lourdes Villardón-Gallego; Concepción Yániz (Universitat Politècnica de València, 2013)
This paper describes a proposal of a Tutoring and Support Plan for PhD students, designed and conducted by the Competences and Values Development Team of Deusto University. This plan aims to provide the training of the members of the research team with strategies and it is also conceived as an alternative to avoid the feeling of loneliness experienced by PhD students while doing their theses as well as to minimize the dropout rate. The basics of the plan are aimed at developing learning autonomy, collaborative work competence on research teams, reflection practising and scientific knowledge construction. The objectives, the main activities and the results based on the opinions of people involved in the Plan are included in this paper. The evaluation of the Plan carried out both by directors and students is positive.